Age at cytomegalovirus, Epstein Barr virus and varicella zoster virus infection and risk of atopy: The Born in Bradford cohort, UK. Issue 6 (28th June 2019) - Pembrey, Lucy; Waiblinger, Dagmar; Griffiths, Paul; Wright, John
Abstract: Background: The prevalence of allergic diseases has increased in recent decades, but the causes remain unclear. Changes in the epidemiology of childhood infections could have contributed, but the current evidence is inconclusive. This study aims to investigate whether age at cytomegalovirus (CMV), Epstein‐Barr virus (EBV) or varicella zoster virus (VZV) infection is associated with the development of atopy. Methods: A total of 2559 children were enrolled in the Born in Bradford Allergy and Infection Study. Serum samples collected at 12 and 24 months were tested for CMV‐IgG, EBV‐IgG and VZV‐IgG for 1000 children to establish age at infection. Skin prick testing (SPT) was conducted at age 4 years. Results: Serology and SPT results were available for 740 children. Of these, 135 (18%) were atopic. In girls, there was a strong association of CMV infection in the second year with increased odds of atopy (adjusted OR 4.38, 95% CI 1.87‐10.29) but this was not observed in boys. Age at EBV or VZV infection was not associated with risk of atopy in unadjusted analysis, but there was effect modification by sex; girls infected with VZV in the second year of life had increased odds of atopy (adjusted OR 2.85, 95% CI 1.29‐6.30). Conclusions: Our results highlight potential sex‐specific effects of age at CMV infection and age at VZV infection on risk of atopy, which provide insight into the mechanisms involved in the development of atopy.